Different intensities of active recovery impair performance during repeated swimming sprints - Toubekis, A.; Tokmakidis, S.; Mavridis, G.; Tahtalis, T. (Pre-olympic Congress 2004. Thessaloniki, Grécia. de 6 a 11 de Agosto de 2004, 2004)
The purpose of the present study was to examine the effect of different active recovery intensities on sprinting performance. Discussion/Conclusions: Sprinting ability of well-trained swimmers decreases when active recovery is performed during the resting interval separating 25 m swimming bouts. The decreased performance is independent of the intensity of active recovery within the range of 50-60% of the 100 m velocity. Active recovery should not be applied during the resting interval of swimming sets designed to improve sprinting ability.